Influence estimation of the inclination angle of the top of the noise protection barrier on its efficiency - Zaets, Vitaly (Technology audit and production reserves, 2021)
The object of research is the sound field from linear sound sources around a rounded noise barrier of the same height and different angles of inclination of the top part of the barrier. It is known that the effectiveness of noise protection barriers depends primarily on the geometric dimensions of the barrier and the relative position of the sound source, barrier and area of noise protection. A large number of publications have been devoted to the study of the influence of these factors and some others, such as the influence of the earth’s surface, sound absorption, sound insulation of the barrier. However, these works did not study the effect of the angle of the top part of the barrier on the change in the barrier efficiency. In this paper, the reduction of sound levels from linear sound sources around noise barriers with different inclination angle of the top part of the barrier is investigated. Rounded barriers of the same height with different radii are considered, which made it possible to simulate barriers in which the top part of the barrier has a different inclination angle. An effectiveness of such barriers for various locations of the sound source, which could also affect the establishment of a pattern of changes in the effectiveness of barriers, is also considered. In addition, the results were analyzed over a wide frequency range. The calculation of the field around such a barrier was carried out using computer simulation using the finite element method. This method allows to easily change the geometric parameters of the barrier and the position of the sound source. The barriers were considered acoustically hard. Thus, an influence of the inclination angle of the top part of the barrier on the sound field around the barrier from various locations of sound sources in a wide frequency range is analysed. The results must be taken into account when designing noise barriers to reduce noise levels from traffic flows